Análisis de factibilidad para establecer un programa de manejo de desechos orgánicos e inorgánicos, en el campus universitario ing. Manuel Haz Álvarez, de la Universidad Técnica Estatal De Quevedo, a partir del año 2013 - Cabezas Haro, Ángela Marcela (2013)
The unit object of the present project forms it the Campus "Manuel Makes Álvarez" of the State Technical University of Quevedo. The situation of the university, in particular of the Campus "Manuel Makes Álvarez" as regards Administration of organic and inorganic waste it is far from the standards of environmental property, since they don't separate the recyclable materials and it lacks places of final disposition adapted with environmental, and alone protection they are remitted in the better of the cases to cover the residuals; far from the norms of hygiene and security; for lack of political decision, increased by the economic crisis and stimulated by the nonexistence of an environmental conscience in the university population that is translated in demand to improve the system. In the investigation he/she was carried out an analysis of the current situation from the environmental and sanitary point of view, especially of contamination of the atmosphere that the daily activities take place. In some places of the university campus a strong activity exists directly in associate constructions with materials, residuals, garbages etc.; in some classrooms and terraces of buildings exist waste and accumulated materials giving a negative visual aspect to the university community, and in general to their visitors; in the gathering of garbage one could observe that the personnel that carries out this works doesn't have the necessary implements for his security; separation of residuals doesn't exist, and in certain cases they separate the materials manually with low value you condition infrahumanas and without any type of necessary protection. One could also observe an informal gathering of residuals carried out by used cartwrights of the university, this situation generates diverse problems in the university, environmental community and of properly this administration. From the point of view of the administration of residuals these recolectors causes some inconveniences as: Breaks of bags. - that although this situation you cannot generalize, they break some recolectors the bags of residuals being spread in the properties of the university. In general the recolectors carries out their work in the same schedule of the academic and administrative activities of the university. From the environmental point of view and sanitarium is determined that a dispersion of construction materials exists and of rejected residuals; proliferation of sanitary vectors, accumulation of desks, bankings and other construction materials. The chapter one is part of the introductory phase of the project containing the problematización, formulation, systematizing, justification, objectives and hypothesis. The chapter two, sustain the theoretical mark of the investigation, the same one that the theoretical concepts of several authors are described. The chapter three contain the methodology of the investigation, sustained in the source, technical, types investigation methods. The chapter four five inform on the opposing conclusions and the recommendations that are suggested for the effectiveness of the project.